Diagnóstico de los factores críticos de éxito en la gestión productiva del sector minorista de lácteos del Cantón Bolívar 2017-2018 - Molina Rengifo, Jessenia Estefanía (2017)
In order to diagnose critical success factors in the productive management of the dairy retail sector in the canton of Bolívar, three methodological phases were carried out, in which the related factors were selected, first to carry out the evaluation, through the theoretical review of Various bibliographic sources, included in the conceptual framework, once these factors were identified, the respective characterization of the productive, then assess the current status of the critical success factors in retail organizations, through certain questions that were used As support for the application of the survey to the retailers, in order to know the degree of compliance that these present against the factors established, in addition, the respective interviews to the owners of the farms, where it was noted that Have the implements necessary for the extraction process Milk processing, conservation and transport of milk is optimal and therefore its derivatives, which allowed to propose before the found circumstance an improvement plan that contributes to a better performance and to the strengthening of the productive management of the dairy retail sector of the canton of Bolivar, for which use was made of the 5W1H matrix, determining who and in what period of time could be corrected criteria that had been classified as a problem.